Geomechanical characterization of volcanic rocks using empirical systems and data mining techniques - Miranda, Tiago F. S. (2018)
This paper tries to characterize volcanic rocks through the development and application of an empirical geomechanical system. Geotechnical information was collected from the samples from several Atlantic Ocean islands including Madeira, Azores and Canarias archipelagos. An empirical rock classification system termed as the volcanic rock system (VRS) is developed and presented in detail. Results using the VRS are compared with those obtained using the traditional rock mass rating (RMR) system. Data mining (DM) techniques are applied to a database of volcanic rock geomechanical information from the islands. Different algorithms were developed and consequently approaches were followed for predicting rock mass classes using the VRS and RMR classification systems. Finally, some conclusions are drawn with emphasis on the fact that a better performance was achieved using attributes from VRS.